Efecto covid 19 en las determinantes de las exportaciones del sector camaronero del Ecuador, año 2020. - Pastor Toala, Joseph Alexander; Loayza Galarza, Cinthia Brigitte (My University, 2021)
This article to analyze the impact that the Covid-19 pandemic has had on shrimp exports in Ecuador by 2020, comparing two scenarios: the first one analyzed shrimp exports for the year 2020 and the second one projected the Shrimp exports assuming the non-existence of Covid-19 by 2020, using the Arima model. The variables observed were pounds exported, income in dollars per pounds exported, and average price per pound. Furthermore, this research is descriptive and longitudinal with a quantitative approach because the behavior of the variables was analyzed and studied during a certain period of time. The results obtained showed that shrimp exports have an increasing trend and when compared with the real data it was verified that the Covid-19 pandemic has generated a significant impact on the variables studied.
El presente artículo analiza el impacto que ha tenido la pandemia del Covid-19 en las exportaciones de camarón en Ecuador para el año 2020, comparando dos escenarios: en el primero se analizaron las exportaciones de camarón del año 2020 y en el segundo se proyectaron las exportaciones de camarón asumiendo la no existencia del Covid-19 para el año 2020, mediante el modelo Arima. Las variables observadas fueron libras exportadas, ingresos en dólares por libras exportadas y precio promedio por libra. Además, esta investigación es de tipo descriptiva y longitudinal con un enfoque cuantitativo porque se analizó y estudió el comportamiento de las variables durante un determinado periodo de tiempo. Los resultados obtenidos demostraron que las exportaciones de camarón tienen tendencia creciente y al compararlos con los datos reales se verificó que la pandemia por el Covid 19-ha generado un impacto significativo en las variables estudiadas.
Keywords: COVID-19; CAMARÓN; MODELO ARIMA